2019
DOI: 10.1590/1413-81232018248.22242017
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between vitamin A supplementation and chronic malnutrition on child development

Abstract: 200 million pre-school age children are not developing properly. Delays in child development are associated with multiple factors. This study aims to analyze if vitamin A supplementation is associated with improved development and how this effect could be mediated by nutritional status. Population-based study surveyed a representative sample of 8000 households, 1232 children 0-35 months, in the state of Ceará, Brazil. The variables analysed included child developmental status, nutritional determinants and conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…A population-based study in Ceará, Brazil was conducted to assess the association between vit. A supplementation and child development using 1,232 children between the age of 0 and 35 months in 8,000 households (71). It was reported that children supplemented with vitamin A showed over 40% lower probability each for delay in development of cognitive and motor abilities, as compared to children without vitamin A supplement.…”
Section: Food Supplementationmentioning
confidence: 99%
“…A population-based study in Ceará, Brazil was conducted to assess the association between vit. A supplementation and child development using 1,232 children between the age of 0 and 35 months in 8,000 households (71). It was reported that children supplemented with vitamin A showed over 40% lower probability each for delay in development of cognitive and motor abilities, as compared to children without vitamin A supplement.…”
Section: Food Supplementationmentioning
confidence: 99%
“…Perlunya konseling gizi dan pendampingan dari tenaga kesehatan secara intensif sejak kehamilan hingga dua tahun pertama kehidupan, terutama pada ibu berpendidikan rendah serta kurang terpapar media massa dan elektronik. Tsaralatifah, 2020), pemberian imunisasi (Ningsih et al, 2020;Permata et al, 2021;Ibrahim et al, 2019;Sartika et al, 2021;Afework et al, 2021;Batiro et al, 2017;Gebre et al, 2019;Fatimah & Chondro, 2020) (Correia et al, 2019). Namun, suplementasi vitamin A dapat memproteksi balita dari penyakit infeksi (Elvandari et al, 2017;Imdad et al, 2017).…”
Section: Abstrakunclassified
“…It yields positive results rapidly and is cost-effective as compared to other interventions such as dietary diversi cation (Beenish et al, 2018;Tam et al, 2020). A population-based study in Ceará, Brazil was conducted to assess the association between VitA supplementation and child development using 1,232 children between the age of 0 to 35 months in 8,000 households (Correia et al, 2019). It was reported that children supplemented with VitA showed over 40% lower probability each for delay in development of cognitive and motor abilities, as compared to children without VitA supplements.…”
Section: Food Supplementationmentioning
confidence: 99%